2021
DOI: 10.1002/tsm2.248
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns in U15 rugby players in Ulster schools: A Rugby Injury Surveillance (RISUS) Study

Abstract: Participation in collision sports such as rugby union has inherent risk of injury. The aim of this study was to examine injury patterns and risk factors in adolescent rugby players (U15 years). A prospective injury surveillance study was undertaken involving 26 schools (599 male rugby players, mean age 14.7years). Data were collected over the 2016/17 playing season, with injuries classified by body part and diagnosis. We explored the association between risk factors (demographic/biometric; injury history, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…6 ). Surface type [ 28 , 49 ], player weight [ 31 , 44 ], previous injury [ 31 , 44 ], previous concussion [ 31 , 44 ], use of regular weight training [ 31 , 44 ], position [ 31 , 50 ], match quarter [ 26 , 27 ], exposure type [ 32 ], season [ 26 ], match volume [ 34 ], history of shoulder dislocation [ 51 ] and rugby itself versus other sports [ 52 , 53 ] were reported as significant risk factors in at least one study (Fig. 6 and Table S14, see ESM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ). Surface type [ 28 , 49 ], player weight [ 31 , 44 ], previous injury [ 31 , 44 ], previous concussion [ 31 , 44 ], use of regular weight training [ 31 , 44 ], position [ 31 , 50 ], match quarter [ 26 , 27 ], exposure type [ 32 ], season [ 26 ], match volume [ 34 ], history of shoulder dislocation [ 51 ] and rugby itself versus other sports [ 52 , 53 ] were reported as significant risk factors in at least one study (Fig. 6 and Table S14, see ESM).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies evaluating primary prevention strategies were found in this review, with two focusing on law changes [ 64 , 65 ], four on equipment use [ 31 , 44 , 62 , 63 ], one on education [ 66 ] and one on neuromuscular training (NMT) [ 30 ]. Of these studies, three focused on the prevention of catastrophic injuries [ 64 – 66 ], three on all injury types [ 30 , 62 , 63 ] and four on head/concussion injuries as the primary injury outcome [ 30 , 31 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are more than 30 school teams with male adolescent rugby players, and 25 registered clubs with dedicated female youth rugby teams, registered across the province of Ulster. Many of these sites have previously been active members of the Rugby Injury Surveillance in Ulster Schools (RISUS) and have successfully collaborated in several previous research studies [ 5 , 9 , 23 ]. We recruited a convenience sample from this sampling frame.…”
Section: Methodsmentioning
confidence: 99%
“…There are more than 30 school teams with male adolescent players, and 25 registered clubs with dedicated female youth teams across Ulster. Many of these sites have previously been active members of the Rugby Injury Surveillance in Ulster Schools and have successfully collaborated in previous studies 4 24 36. To be eligible for inclusion, participants must be (1) aged between 16 years and 18 years, (2) injury free at the time of recruitment and (3) currently playing rugby union in the 2022/23 playing season.…”
Section: Introductionmentioning
confidence: 99%